Usability Evaluation of User Requirement–Based Teleconsultation Robots: A Preliminary Report from South Korea - Lee, Hyeongsuk; Kim, Jeongeun; Kim, Sukwha; Kong, Hyoun-Joong; Joo, Hyunjin; Lee, Dongkyun; Ryu, Hyeongju (Methods of Information in Medicine, 2020)
Background Telepresence robots used to deliver a point-of-care (POC) consultation system that may provide value to enable effective decision making by healthcare providers at care sites.Objectives This study aimed to evaluate usability of teleconsultation robots, based on endusers' needs, that can improve acceptance in future robot applications.Methods This is a single group postdesign study using mixed methods to assess the usability of teleconsultation robots using scenarios. To collect opinions from various departments, 15 nurses or physicians currently working at medical institutions in Korea were selected using purposive sampling. The usability evaluation was conducted on healthcare providers twice at the simulation center; the think-aloud method was used and surveys and interviews were conducted to identify problems or improvements that may arise from the use of robots in hospital settings.Results The results showed that perceived usefulness, perceived ease of use, and satisfaction level each scored 4 points or higher out of 7 points, showing usability of midhigh level. Camera angle control and robot driving functions were the most difficult. Other basic robot user interface was shown to be relatively easy. There was no difference in usability depending on the characteristics of the evaluator. Some functions including user interface were modified based on the usability test.Conclusion Using robots in health care institutions may support effective communication among healthcare providers, thus contributing to health care improvement.
Keywords: point-of-care system; remote consultation; telerobotics; telemedicine